Analisis Strategi Bauran Pemasaran (4P) Dalam Pencapaian Target Penjualan Pada The Pottery Coffee Di Pondok Pinang Jakarta Selatan - Rahmathun Najilah; Munarsih Munarsih (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
Abstract - The purpose of this study was to analyze the marketing mix strategy (4P) in achieving sales targets at The Pottery Coffee in Pondok Pinang, South Jakarta, using a SWOT analysis approach. The company experienced declining revenue due to increasingly fierce competition among coffee shops. The research took place at The Pottery Coffee in Pondok Pinang, South Jakarta, located at Jl. H. Saikin No. 13 Selapa, Polri, RT.8/RW.8, Lb. Bulus, Pondok Pinang, South Jakarta City, Special Capital Region of Jakarta 12310. This study used a qualitative descriptive method. Data collection techniques included observation, interviews, and documentation, which were then analyzed using SWOT analysis. The analysis results showed that the IFAS score was 0.98 and the EFAS score was 0.82, placing the SWOT matrix in quadrant I of the aggressive strategy. This strategy indicates that The Pottery Coffee has strong internal strengths and numerous external opportunities that support aggressive growth.